Enhanced predictive method for pipeline strain demand subject to permanent ground displacements with internal pressure & temperature: a finite difference approach - Allouche, Ismael; Zheng, Qian; Yoosef-Ghodsi, Nader; Fowler, Matthew; Li, Yong; Adeeb, Samer (Journal of Infrastructure Intelligence and Resilience, 2023)
Pipelines subject to ground deformations generated by geohazard loads carry high importance on pipeline analysis, design, and assessment due to risk of structural damage or failure. Additionally, internal pressure and temperature variation within an operating pipe induce additional strains in combination with pipe strains generated by ground displacement. In this study, an enhanced predictive method is proposed founded upon methods employed by Zheng et al. (2022) to assess pipeline behaviour subject to permanent ground displacement, while considering effects of internal operating pressure and temperature variation. The finite difference-based method previously proposed for strain analysis of buried steel pipes subject to ground movement ignores the effects of internal pressure and/or temperature loading, limiting the applicability of this approach to exclude the operating conditions of pipelines. To address this limitation, the proposed enhanced method accounts for the initial thermal strains and biaxial stress state in the pipe due to hoop stress generated by internal pressure. These additional strains are considered within the expressions of internal axial force and bending moment, derived based on the actual stress distribution on the pipe cross-section. The accuracy of the proposed method is validated against the finite element method (FEM) with respect to results of strain and deformation demand using several indicative case studies. This research provides an effective method of incorporating temperature and internal pressure loads of pipelines subject to permanent ground displacements of varying types, magnitudes, and directions.